Sustainable Development Goals Reporting and Company Performance of Listed Companies in Sri Lankan Service Sector - Ekanayaka, E.M.S.K.; Kethmi, G.A.P. (Department of Finance, Faculty of Commerce and Management Studies University of Kelaniya Sri Lanka, 2024)
Introduction: The ability of sustainable development to address urgent economic, social, and environmental concerns while preserving the welfare of current and future generations has led to its evolution into a worldwide imperative. As a developing country, in the Sri Lankan context, the SDGs hold particular relevance due to the country's efforts to overcome poverty, improve healthcare and education, enhance gender equality, and promote sustainable resource management. This study investigated the relationship between Sustainable Development Goals (SDG) reporting and the financial performance of listed companies in the Sri Lankan service sector under two sectors financial and non-financial. Methodology: Return on Assets and Return on Equity are used as dependent variables to measure the Financial Performance whilst the Sustainable Development Goals Index is used as the independent variable to measure the level of Sustainability Reporting. Firm Size is used as a control variable. Data of 50 service sector companies listed on the Colombo Stock Exchange for the period from 2018 to 2022 using the annual reports of these companies. The data is analyzed using descriptive statistics, correlation analysis and regression analysis employing the STATA software under two sub-sectors financial and non-financial. Findings: The findings indicate a complicated and nuanced link between SDG focus and company performance in Sri Lanka's service sector. While a positive relationship for financial companies' ROE was shown, it lacked statistical significance. A weak and statistically insignificant negative association is observed for financial companies ROA and Non-financial companies, on the other hand, revealed a statistically significant negative relationship between the weighted SDG index and both ROE and ROA. Further, the regression model revealed that the SDG index has a positive and a negative impact on ROE and ROA respectively for financial companies while the SDG index has a negative impact on both ROE and ROA for non-financial companies. Conclusion: Traditional financial metrics may not capture all of the long-term advantages of sustainable practices, but short-term costs, industry dynamics, and methodological issues can all have an influence on the connection. To comprehend the complex relationship and to develop solutions for sustainable business practices, further study, comprehensive information, long-term analysis, and industry-specific studies are required. Pursuing sustainability is about setting up a resilient, equal, and successful future for all stakeholders, not simply increasing profits. In conclusion, this study calls for more investigation into the underlying causes and possible long-term advantages of SDG activities in non-financial firms.
Keywords: Sustainable Development Goals, Company Performance, ROA, ROE